Trends in private investment in developing countries : Statistics for 1970-97 and Perceived Obstacles to Doing Business - Pfeffermann, Guy Pierre, 1941- 1941- (The World Bank, 1999)
This is the tenth annual edition of "Trends in Private Investment in Developing Countries." To mark this event, this report includes figures for each of the countries for which data are available as well as the first country-specific results of a worldwide survey on obstacles to doing business perceived by executives in 74 countries (including several industrial countries for comparison). The first part of this report documents trends in private and public fixed investment. The second part presents country-specific results of a 1996/97 worldwide survey of business executives. The discussion focus on obstacles to doing business and their relationship to levels of private investment. A few factors emerge as being of particular importance to private investment decisions:the real exchange rate, the rule of law, predictability of judiciary systems, and the extent to which financing is available to enterprises